Trastuzumab and pertuzumab combination therapy for advanced pre-treated HER2 exon 20-mutated non-small cell lung cancer. (August 2022) - van Berge Henegouwen, J.M.; Jebbink, M.; Hoes, L.R.; van der Wijngaart, H.; Zeverijn, L.J.; van der Velden, D.L.; Roepman, P.; de Leng, W.W.J.; Jansen, A.M.L.; van Werkhoven, E.; van der Noort, V.; van der Wekken, A.J.; et al.
Abstract: Introduction: In 1–3% of non-small cell lung cancer (NSCLC) human epidermal growth factor 2 ( HER2 ) mutations are identified as a genomic driver. Nevertheless, no HER2 -targeted treatment is approved for NSCLC. In the Drug Rediscovery Protocol (DRUP), patients are treated with off-label drugs based on their molecular profile. Here, we present the results of the cohort 'trastuzumab/pertuzumab for HER2 exon20 mutation positive ( HER2m+ ) NSCLC'. Methods: Patients with treatment refractory, advanced HER2m+ NSCLC with measurable disease (RECISTv1.1) were eligible. Treatment with intravenous trastuzumab combined with pertuzumab every 3 weeks was administered. The primary end-point was clinical benefit (CB: either objective response or stable disease ≥ 16 weeks). Patients were enrolled using a Simon-like 2-stage design, with 8 patients in stage 1 and up to 24 patients in stage 2 if at least 1 patient had CB in stage 1. At baseline, a biopsy for biomarker analysis, including whole genome sequencing, was obtained. Results: Twenty-four evaluable patients were enrolled and treated between May 2017 and August 2020. CB was observed in 9 patients (38%); including an objective response rate of 8.3% (2 patients had a partial response) and 7 patients with stable disease ≥ 16 weeks. The most frequently observed HER2 mutation was p.Y772_A775dup (71%, n = 20). Median follow-up was 13 months, median progression-free survival and overall survival 4 (95% CI 3–6) and 10 months (95% CI 4 – not reached), respectively. Whole genome sequencing data (available for 67% of patients) confirmed the inclusion mutation in all cases. No unexpected toxicity was observed. Conclusion: Despite the fact that the study did meet its primary end-point, trastuzumab/pertuzumab was only marginally active in a subset of patients with heavily pre- treated HER2m + NSCLC. Highlights: In 1–3% of patients with non-small cell lung cancer human epidermal growth factor 2 mutations are identified as genomic driver. The most frequently observed human epidermal growth factor 2 mutation is p. Y772_A775dup. Trastuzumab/pertuzumab treatment was beneficial in 38% of the included patients. Whole genome sequencing data revealed that patients with benefit had less potential drivers detected. Toxicities were similar to those previously observed in pivotal trials.